2021
DOI: 10.1016/j.plabm.2021.e00256
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: Detection of free monoclonal light chains by modified immunofixation electrophoresis with antisera against free light chains

Abstract: Introduction Neoplastic monoclonal gammopathies are frequently associated with production of excess free monoclonal light chains. A sensitive method for detecting free monoclonal light chains in serum could provide a marker for residual/minimal residual disease and as an adjunct to serum protein electrophoresis to serve as a screening method for monoclonal gammopathies. Methods Conventional serum immunofixation electrophoresis was modified by applying undiluted serum sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…This need for accurate background information was highlighted in the study by Wilhite et al where they reported that a sample tested by MASS-FIX at the Mayo clinic was reported to contain elotuzumab when the patient was not being treated with this tmAb. 63 The identification of a light chain with a m/z consistent with a tmAb does not definitively confirm that presence of the tmAb and should be reviewed in the context of the medical and treatment history.…”
Section: Provides Greater Sensitivity For the Detection Of Low-level ...mentioning
confidence: 98%
See 4 more Smart Citations
“…This need for accurate background information was highlighted in the study by Wilhite et al where they reported that a sample tested by MASS-FIX at the Mayo clinic was reported to contain elotuzumab when the patient was not being treated with this tmAb. 63 The identification of a light chain with a m/z consistent with a tmAb does not definitively confirm that presence of the tmAb and should be reviewed in the context of the medical and treatment history.…”
Section: Provides Greater Sensitivity For the Detection Of Low-level ...mentioning
confidence: 98%
“…There are case examples where MASS-FIX outperformed Freelite 61 and other cases where Freelite provided greater sensitivity. 62,63 In light of the variable sensitivity for the detection of monoclonal FLC compared to the serum FLC assays, it is important that serum FLC and BJP assessments continue to be used alongside the MALDI-TOF MS assays that do not include reagents specifically designed for the detection of monoclonal FLC.…”
Section: I N Ica L Pe R For M a Nce Of Th E M A L Di-tof Ms Assays Fo...mentioning
confidence: 99%
See 3 more Smart Citations